2021
DOI: 10.1038/s41598-021-92362-1
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning enhances the performance of short and long-term mortality prediction model in non-ST-segment elevation myocardial infarction

Abstract: Machine learning (ML) has been suggested to improve the performance of prediction models. Nevertheless, research on predicting the risk in patients with acute myocardial infarction (AMI) has been limited and showed inconsistency in the performance of ML models versus traditional models (TMs). This study developed ML-based models (logistic regression with regularization, random forest, support vector machine, and extreme gradient boosting) and compared their performance in predicting the short- and long-term mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…But this can be alleviated by advancing the increasing use of digital strategies aimed at enhancing the participation of patients and healthcare providers in integrated healthcare management. [13][14][15][16][17] Incorporation of such ML models into electronic health records may help the scalability of prevention strategies and improved management in terms of healthcare cost savings and better quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…But this can be alleviated by advancing the increasing use of digital strategies aimed at enhancing the participation of patients and healthcare providers in integrated healthcare management. [13][14][15][16][17] Incorporation of such ML models into electronic health records may help the scalability of prevention strategies and improved management in terms of healthcare cost savings and better quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…By developing ML solutions as hands-on approaches to precisely predict in-real time the disease prognosis, this direction empowers robust personalized medicine decisions for specific populations, or individual patients, in the clinical setting. Previous efforts aiming to advance the application of ML prediction models in CVDs have been previously executed in patients suffering from ST-elevated myocardial infarction (STEMI) ( 30 ) and non-ST-segment elevation myocardial infarction (non-STEMI) ( 31 ).…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…In 2021, Lee et al constructed machine learning methods by logistic regression with regularization, random forest, support vector machine, and extreme gradient boosting to construct 3-month, 12-month, and in-hospital mortality prediction models for AMI patients. The results showed that machine learning outperformed traditional prediction models [ 46 ]. In 2022, Xiao et al employed six machine learning methods to construct predictive models for the occurrence of major adverse cardiovascular events (MACEs) in AMI patients.…”
Section: Discussionmentioning
confidence: 99%